1999
DOI: 10.1176/ps.50.8.1036
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy and Causes of Death in a Population Treated for Serious Mental Illness

Abstract: Findings in this study are consistent with previous findings identifying excess mortality in a population with serious mental illness. The high rate of injury deaths, especially those due to psychotropic and other medications, should concern providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(87 citation statements)
references
References 24 publications
6
78
1
2
Order By: Relevance
“…In this study, neither mental illness nor health literacy was associated with mortality. This observation is not what would be expected based on prior research, 47,48 and may be because of competing mortality risks in the sample. In addition, we did not assess knowledge of overdose risk or prevention knowledge, which could have been associated with death.…”
Section: Discussioncontrasting
confidence: 93%
“…In this study, neither mental illness nor health literacy was associated with mortality. This observation is not what would be expected based on prior research, 47,48 and may be because of competing mortality risks in the sample. In addition, we did not assess knowledge of overdose risk or prevention knowledge, which could have been associated with death.…”
Section: Discussioncontrasting
confidence: 93%
“…(E-mail: s.metraux@usp.edu) takes on spatial dimensions, as research identifies Harlem both as a neighborhood that disproportionately generates homelessness, 11 and has elevated mortality rates 12 to the point where, according to one study, men in Bangladesh had better prospects of reaching age 65 than African-American men in Harlem. 13 The homeless population also features other characteristics that are associated with increased mortality hazard, including poorer overall health; 14 mental illness; [15][16][17] substance abuse; [18][19][20][21] incarceration; [22][23][24] and adverse childhood experiences. 25,26 Pointing to the overrepresentation of these conditions, however, must also come with the acknowledgment that these conditions are invariably found only among minorities of the homeless population.…”
Section: Introductionmentioning
confidence: 99%
“…32 In the United States, high rates of death, and especially of fatal injury, have also been reported in people treated with antipsychotics. 33 Further, a study from Finland found that the number of antipsychotic drugs used correlated with mortality, the relative risk increasing by 2.50 per prescribed drug. 34 Shortly after phenothiazines were introduced for the treatment of schizophrenia, they were already shown to elevate serum triglyceride and total cholesterol levels.…”
Section: Mortalitymentioning
confidence: 99%